Effect of a multimedia training programme for pain management on pain intensity and depression in patients with non-specific chronic back pain - Shaygan, Maryam; Jaberi, Azita; Firozian, Roghayyeh; Yazdani, Zahra; Zarifsanaiey, Nahid (Investigación y Educación en Enfermería, 2023)
Objective. To determine the effect of multimedia training on pain intensity and depression in patients with chronic low back pain. Methods. In this randomized controlled trial study, the intervention group was trained about pain management consisted of communication skills, assertiveness, stress management, lifestyle enhancement skills and physical activity prepared in seven CDs using multimedia method and the control group received routine training included physician’s visits, medication prescriptions and receiving the recommendations of the physician and healthcare providers. Beck Depression Inventory and Jensen Pain Questionnaire were completed for the two groups in three stages: pre-training, post-training and 2 months thereafter. Results. The results showed that there were no significant statistical difference between two groups in terms of demographic variables indicated homogeneity of research groups. Repeated measure ANOVA showed that the mean scores of pain intensity and depression changed significantly over time in both control and intervention groups (p<0.001); however, the effect of the group was not significant (p=0.565, p=0.748, respectively). Hence, the results of time-group interaction showed that there was significant difference between the two groups in terms of pain intensity and depression (p<0.001, p=0.003, respectively). The effect size revealed that the difference between mean scores of depression before and after the intervention in the both group was high (1.04 and 1.45, respectively). Conclusion. The study results indicated that multimedia training has the potential in relieving pain intensity and depression in patients with non-specific chronic low back pain.